2014
DOI: 10.1097/01.pra.0000450318.14236.36
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Cognitions about Sleep in Psychiatric Patients

Abstract: The optimal management of sleep problems is a significant challenge, particularly in patients with psychiatric illness, because disturbed sleep is a known risk factor for relapse. This study used the short Dysfunctional Beliefs and Attitudes Scale to assess beliefs about sleep in adults with acute psychiatric disorders (N=100) recruited from inpatient and outpatient clinics. The subjects showed highly dysfunctional beliefs and attitudes about sleep and held diverse opinions about, but had low confidence in, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…We think this is likely, based on recent research revealing that many individuals with serious mental illnesses prefer to be engaged in shared decision-making regarding mental health treatments, particularly to be offered options and asked their opinions about treatment options [72,73]. Furthermore, a recent study found that people receiving active treatment for psychiatric illnesses (e.g., schizophrenia spectrum, affective, neurotic, stress-related, and somatoform disorders) expressed a desire to partake in behavioral sleep treatments [70]. Future research is needed to investigate the specific treatments that people with schizophrenia spectrum disorders desire and how providers can collaborate with clients to optimally partake in shared decisionmaking around sleep treatment decisions in a manner that capitalizes on their self-identified needs and motivation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We think this is likely, based on recent research revealing that many individuals with serious mental illnesses prefer to be engaged in shared decision-making regarding mental health treatments, particularly to be offered options and asked their opinions about treatment options [72,73]. Furthermore, a recent study found that people receiving active treatment for psychiatric illnesses (e.g., schizophrenia spectrum, affective, neurotic, stress-related, and somatoform disorders) expressed a desire to partake in behavioral sleep treatments [70]. Future research is needed to investigate the specific treatments that people with schizophrenia spectrum disorders desire and how providers can collaborate with clients to optimally partake in shared decisionmaking around sleep treatment decisions in a manner that capitalizes on their self-identified needs and motivation.…”
Section: Discussionmentioning
confidence: 92%
“…Sleep plays an important role in cognitive, brain, immune, metabolic, and cardiovascular functions, each of which are generally compromised in people with schizophrenia spectrum disorders; furthermore, they find sleep disorders distressing and are motivated to try new solutions [70,71]. More research is needed to tailor and implement nonpharmacological sleep treatments to make them maximally effective in people with schizophrenia spectrum disorders, as well as examine new directions for pharmacological intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that cognitive behavioral therapy for insomnia could be used to target suicide risk prevention and intervention (31). Moreover, dysfunctional beliefs and high concern about sleep offer potential targets for psychotherapy of mental health and suicidal behavior (34,48). In any event, further studies are required to determine whether sleep screening/interventions, incorporating global sleep problems or more specific sleep domains, are effective in suicide treatment or prevention.…”
Section: Implicationmentioning
confidence: 99%
“…There has been little research on subjective sleep experiences and beliefs among patients with various psychiatric disorders. To the best of our knowledge, a study by Huthwaite et al (2014) was the only study that explored subjective sleep experiences among patients with a range of psychiatric disorders and looked into dysfunctional sleep beliefs. Therefore to address the gaps in sleep literature, this study aimed to gain insights into dysfunctional sleep beliefs among psychiatric patients by exploring sociodemographic and clinical factors which are associated with dysfunctional sleep beliefs, and examining the associations between these beliefs and insomnia among psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%